Hambling, Jack part 2. Interview about growing up on Cable Avenue in Bay Roberts. - Wilson, Lisa (2013)
Bishop of Bay Roberts; John Bishop’s mill; Story about Uncle drinking rum with friends; Trees on Cable Ave.; Wartime on Cable Ave.; Cable Ave. as a unique place; Manager named Cameron; Sliding on the Ave.; Trading books with his daughter; Chester Smith gave a set of cricket pads